2015
DOI: 10.1111/zoj.12220
|View full text |Cite
|
Sign up to set email alerts
|

Operational criteria for cryptic species delimitation when evidence is limited, as exemplified by North AmericanEntomobrya(Collembola: Entomobryidae)

Abstract: Evaluating species boundaries remains a significant challenge in rare, difficult to collect, and/or understudied groups because of a lack of available data. Uninformative morphology, unknown ecologies and/or geographical distributions, inadequate comparative sequence data, and limited sample sizes present substantial challenges when applying commonly used methods for species delimitation. Here we present an approach that overcomes the challenges previously mentioned by integrating phylogeny, genetic distances,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 102 publications
2
57
0
3
Order By: Relevance
“…n. 1 and Entomobrya sp. n. 2 in Katz et al (2015). The cryptic lineages of Entomobrya quadrilineata color forms B, C, and D in Katz et al (2015) are identified as Entomobrya decemfasciata .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…n. 1 and Entomobrya sp. n. 2 in Katz et al (2015). The cryptic lineages of Entomobrya quadrilineata color forms B, C, and D in Katz et al (2015) are identified as Entomobrya decemfasciata .…”
Section: Methodsmentioning
confidence: 99%
“…For some groups, however, uncertain homology, intraspecific variation, and characters of difficult observation have limited the utility of morphological characters as tools for species diagnosis and phylogenetic inference. Recent advances in DNA sequencing technology have provided scientists with additional ways to delimit groups that lack informative morphology, such as cryptic species complexes (Frati et al 1994, 1995, 2000; Carapelli et al 1995, 2005; Simonsen et al 1999; Soto-Adames 2002; Burkhardt and Filser 2005; Cicconardi et al 2010, 2013; Felderhoff et al 2010; Porco et al 2012; Zhang et al 2014c; Katz et al 2015), but in practice most species diagnosis remains dependent on fixed characters, only obtained by rigorous morphological examination (Will and Rubinoff 2004). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…are not directly practicable. Morphological stasis or overlapping intra-and interspecific character variability often confuse interpretation of species (hypotheses) and confound conventional species delimitation approaches (de Queiroz 2007, Katz et al 2015. In our case with subterranean ellobioid microsnails, integrative taxonomy provides the most tangible answer to this problem since it pulls together data derived from different data sources including comparative morphology, genetics, ecology and geology to enable inferences about founded, but sketchy species hypotheses.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, species delimitation, the practice of recognizing and determining species boundaries, has expanded to evaluate the current inflation of species concepts generated to infer biological information (de Queiroz 2000, Katz et al 2015). Speciation is an ongoing process influencing traits at varying temporal scales.…”
Section: Introductionmentioning
confidence: 99%